2019
DOI: 10.1108/intr-12-2017-0530
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selfie promotion and celebrity endorsed advertisement on decision-making processes

Abstract: Purpose The purpose of this paper is to assess the effect of two promotional methods, namely, celebrity endorsed advertisement and selfie promotion, on customers’ decision-making processes using the AISAS model. Design/methodology/approach A within-subject experimental design was used to observe how young adults in Malaysia would respond to two promotional methods about a new seafood restaurant. A total of 180 responses were collected using a structured questionnaire. Data were assessed and analysed using pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 112 publications
3
90
1
2
Order By: Relevance
“…The linear influence relationships (attention → interest → search → action → share) of the AISAS were significantly positive, while only some of the nonlinear influence relationships were significant and weaker than the linear ones. These results are consistent with those of Hendriyani et al and Cheah et al, and also verify that the AISAS model is more suitable than AIDMA for explaining the behavioral characteristics of tourism consumers in the Internet era [56,76].…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The linear influence relationships (attention → interest → search → action → share) of the AISAS were significantly positive, while only some of the nonlinear influence relationships were significant and weaker than the linear ones. These results are consistent with those of Hendriyani et al and Cheah et al, and also verify that the AISAS model is more suitable than AIDMA for explaining the behavioral characteristics of tourism consumers in the Internet era [56,76].…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Hendriyani et al used the AISAS model to analyze the online consumer behavior of Twitter users and found that there were positive relationships between attention and interest, interest and search, and search and behavior [56]. Cheah, Ting, Cham, and Memon applied AISAS to compare the effect of celebrity-endorsed advertising and selfie promotion and found that the AISAS model with selfie promotion produced better predictive ability while attention had a positive impact on interest, interest on search, search on behavior, and behavior on sharing [76]. Therefore, the following hypotheses were proposed: Hypotheses 1 (H1).…”
Section: The Aidma and Aisas Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive results were derived by Hu et al ( 2002 ) and Luk and Yip ( 2008 ) that established trust would improve the promotion effectiveness and further influence the final purchasing motivation and intention. Nevertheless, many changes have taken place since the last decade in the e-commerce arena such as the increase in digital buyers, the pervasiveness of social media and further advancement in technology (Cham et al 2016 ; Cheah et al 2019 ). Thereupon, this research is carried out to re-examine the trust-based recommendation system on product promotion effectiveness toward current generation of digital buyers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies also investigate subjects related to personalization and customization, such as the use of mobile applications and various communication tactics to enhance business performance and facilitate consumer's decisions and experience (Cheah, Ting, Cham & Memon, 2019;Steinhoff et al 2019). Personalization is effective in the current environment as organizations have access to large volume of data on customer's purchase behaviour, website browsing, and preferences that can be analysed to create customer profiles (Liu-Thompkins, 2019;Schreiner, Rese & Baier, 2019;Shanahan, Tran & Taylor, 2019;Strycharz, van Noort, Helberger & Smit, 2019).…”
Section: Brief Review Of Recent Marketing Literaturementioning
confidence: 99%